2012
DOI: 10.1051/0004-6361/201118506
|View full text |Cite
|
Sign up to set email alerts
|

Multifrequency study of GHz-peaked spectrum sources and candidates with the RATAN-600 radio telescope

Abstract: Context. Gigahertz peaked spectrum (GPS) radio sources are a class of extragalactic radio sources characterized by a spectral peak in the gigahertz domain. They are a mixed class of quasars and galaxies. A large proportion of the sources studied in the literature have only few data points in the radio domain, and the determination of variability and shape of the simultaneous spectra is inadequate. Sources currently included in the GPS source lists are very heterogeneous. Aims. We present the observational resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 31 publications
2
60
0
Order By: Relevance
“…In particular, high fraction of CSS radio galaxies are not variable, while only ∼30% of GPS/HFP galaxies preserve the convex spectrum (Torniainen et al 2007, Hancock et al 2010. The majority of the CSS, GPS, and HFP quasars show significant flux density and spectral variability (Mingaliev et al 2012, Orienti et al 2007). Spectral changing and flux density variability do not always imply that the source is part of the blazar population, rather than a genuine CSS/GPS/HFP object.…”
Section: Variabilitymentioning
confidence: 99%
“…In particular, high fraction of CSS radio galaxies are not variable, while only ∼30% of GPS/HFP galaxies preserve the convex spectrum (Torniainen et al 2007, Hancock et al 2010. The majority of the CSS, GPS, and HFP quasars show significant flux density and spectral variability (Mingaliev et al 2012, Orienti et al 2007). Spectral changing and flux density variability do not always imply that the source is part of the blazar population, rather than a genuine CSS/GPS/HFP object.…”
Section: Variabilitymentioning
confidence: 99%
“…As the 1.4 GHz NVSS and 325 MHz WENSS images show that the nearest neighbour is at a distance of 232 arcsec from J1606+3124 and based on the probabilities of the sources 6 http://third.ucllnl.org/cgi-bin/firstcutout being side lobes, we conclude that the five neighbouring sources in the 1.4 GHz FIRST image are all image artefacts. We matched J1606+3124 to sources in the 0.96, 2.3, 3.9, 7.7, 11.2 and 21.65 GHz catalogues of Kovalev et al (1999) and the 1.1, 2.3, 4.8, 7.7, 11.2 and 21.7 GHz catalogues of Mingaliev et al (2012). However, since these observations were taken with the RATAN-600 telescope, the resolution of all of the observations is lower than the distance to the nearest neighboring source.…”
Section: J1606+3124mentioning
confidence: 99%
“…From this they concluded that J1606+3124 is not variable. While we discarded the matches to Mingaliev et al (2012), we note that the authors did observe J1606+3124 six times with the RATAN-600 telescope between 2006 July and 2010 May at 21.7, 11.2, 7.7, 4.8 and 2.3 GHz, and five times at 1 GHz over the same period. These observations also indicate that J1606+3124 is not variable at these frequencies.…”
Section: J1606+3124mentioning
confidence: 99%
“…The experimental data were processed using the modules of the FADPS (Flexible Astronomical Data Processing System) standard reduction package by Verkhodanov (); this is a reduction system for data from the broadband continuum radiometers of the RATAN‐600 secondary mirror. The processing methods are described in Mingaliev et al () (). The following eight flux density calibrators were used to calculate the calibration coefficients in the scale by Baars et al (): 3C48, 3C138, 3C147, 3C161, 3C286, 3C295, 3C309.1, and NGC 7027.…”
Section: Observationsmentioning
confidence: 99%